COMPARATIVE STUDY OF AMINO ACID COMPOSITION IN THE DIFFERENT VARIETIES OF WATERMELON (CITRULLUS VULGARIS) SEEDS SOLD IN KANO METROPOLIS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This research looked into the different varieties of watermelon (citrullus vulgaris) seeds sold in Kano metropolis to determine their qualitative and quantitative composition of amino acids using the Multi –sequential sample amino acid analyzer. Seventeen (17) amino acids were found and nine (9) among them were essential amino acids. The most concentrated essential amino acid (g/100g protein) are lysine in Dan – Bunkure  and leucine in Dan – Maiduguri and Dan – Niger varieties. Glutamic was found to be the dorminant  amino acid in all the seed varieties . The least concentrated amino acid content in all the seed varieties is methionine. The Dan – Maiduguri variety has proved to be the best with the highest content of total amino acids (82.38g/100g protein) and the highest content of leucine (6.57g/100g protein). These seed varieties of citrullus vulgaris are good sources of essential and non – essential amino acids and can be used as animal feed supplement and adult health supplement.
Keywords: Citrullus vulgaris, Watermelon seeds, Amino acid composition